2017
DOI: 10.1155/2017/7101694
|View full text |Cite
|
Sign up to set email alerts
|

Spontaneous Bilateral Sternoclavicular Joint Septic Arthritis and Lumbar Discitis: An Unusual Case in a Healthy Adult

Abstract: Introduction Septic arthritis of the sternoclavicular (SC) joint is a rare condition. Typically, it presents in patients with risk of infection and is usually unilateral. In this report, we describe a case of spontaneous bilateral sternoclavicular joint infection of an otherwise healthy adult. Case Presentation A 67-year-old man presented in our hospital complaining of 2-week history of neck and chest pain which was radiating to his shoulders bilaterally. Clinical examination revealed erythema and swelling of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 21 publications
0
5
0
Order By: Relevance
“…Most cases of epidural abscesses/phlegmons are related to episodes of an invasion of skin flora (e.g., therapeutic injections), with S. aureus identified in approximately two-thirds of cases [ 21 - 23 ]. We only found two previously published cases that reported concurrent SCJ infection and some form of epidural/paraspinous infection (abscess, phlegmon, and/or discitis) [ 13 , 14 ]. Shioya N et al [ 13 ] described a 61-year-old male with poorly controlled diabetes who developed a lumbar epidural abscess and SCJ infection from epidural injections for an L4-L5 disc herniation.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Most cases of epidural abscesses/phlegmons are related to episodes of an invasion of skin flora (e.g., therapeutic injections), with S. aureus identified in approximately two-thirds of cases [ 21 - 23 ]. We only found two previously published cases that reported concurrent SCJ infection and some form of epidural/paraspinous infection (abscess, phlegmon, and/or discitis) [ 13 , 14 ]. Shioya N et al [ 13 ] described a 61-year-old male with poorly controlled diabetes who developed a lumbar epidural abscess and SCJ infection from epidural injections for an L4-L5 disc herniation.…”
Section: Discussionmentioning
confidence: 99%
“…SCJ, blood, and urine cultures grew S. aureus, but the subsequent aspiration of the epidural abscess showed no growth. Mamarelis G et al [ 14 ] reported the case of a 67-year-old male with a medical history of hypertension and gout that developed bilateral SCJ septic arthritis and lumbar discitis (there was no antecedent injection). Surgery and aspirations were not done for the spine or SCJ infections.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Unilateral SCJI can often present with fever, joint swelling, warmth and immobility. Bilateral infections can present as a butterfly rash on the chest (19). Some unusual presentations have also been reported in literature, such as a pressure like chest pain radiating to the neck or shoulder.…”
Section: Medical History and Physical Exammentioning
confidence: 92%
“…The presentation of SCJ septic arthritis can present as chest pain radiating down the arm. The low prevalence and ambiguous presentation of SCJ often delay its diagnosis of septic arthritis [ 6 , 7 ]. Currently, no standardized diagnostic and therapeutic algorithms for SCJ infection exist, as defined in the literature [ 8 ].…”
Section: Introductionmentioning
confidence: 99%